A national survey of Australian midwives' birth choices and outcomes. Issue 2 (March 2023) - Coulton Stoliar, S.; Dahlen, H.G.; Sheehan, A.
Abstract: Background: Maternity care in Australia is predominantly provided by midwives, many who give birth. There is a paucity of research on midwives' own childbearing preferences and experiences. Aim: To explore midwives childbirth preferences and outcomes when giving birth to their first child in Australia, after qualifying as a midwife. Methods: An online national survey. Data were analysed using descriptive statistics. Findings: 447 midwives responded, with the majority of midwives indicating a preference for a normal vaginal birth with a known care provider under a continuity of midwifery care model. For midwives who were first time mothers, 66% had normal vaginal births, 16.3% had an instrumental birth, and 16.8% had caesarean births. Over 85% of midwives received the model of care they wanted and 45% had continuity of midwifery care. While a quarter of midwives wanted a homebirth, 11.2% achieved this. Over three quarters (75.4%) of midwives were cared for by a care provider of their choosing. Discussion: There was a difference in models of care accessed and birth outcomes between midwives and other women giving birth for the first-time in Australia. Australian midwives appear to have the advantage of clinical and scientific knowledge to navigate the maternity care system to get the birth care and outcomes they want. Conclusion: It is possible that professional experience, insider knowledge, and existing relationships with other midwifery friends and colleagues, affords midwives a higher degree of agency and autonomy when it comes to getting the maternity care and birth outcomes that they want.